Penerapan Metode Class Based Storage pada Gudang Penyimpanan Barang Jadi PT. XYZ - Purnomo, Hendra Arya; Talitha, Tita (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Warehouses play a crucial role in the supply chain of the manufacturing industry as centers for storage, distribution, and inventory management. PT. XYZ faces inefficiencies in its randomized storage system, leading to increased item retrieval time, extended worker travel distances, and reduced operational efficiency. This study aims to analyze and redesign the warehouse layout using the Class Based Storage method and ABC Classification to improve storage and retrieval efficiency. Items were classified using the ABC method, where category A accounted for 72.77% of total movements, category B 16.69%, and category C 10.54%. Based on the implementation of the Class-Based Storage method and ABC Classification, the proposed warehouse layout positions category A items near the I/O point, followed by categories B and C, to shorten retrieval distances, reduce item search time, and enhance overall warehouse operational efficiency.